2021
DOI: 10.1097/shk.0000000000001762
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressor Responsiveness Beyond Arterial Pressure: A Conceptual Systematic Review Using Venous Return Physiology

Abstract: We performed a systematic review to investigate the effects of vasopressor-induced hemodynamic changes in adults with shock. We applied a physiological approach using the interacting domains of intravascular volume, heart pump performance, and vascular resistance to structure the interpretation of responses to vasopressors. We hypothesized that incorporating changes in determinants of cardiac output and vascular resistance better reflect the vasopressor responsiveness beyond mean arterial pressure alone. We id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Another study reported that Pmsf was 12 mmHg 1 minute after cardiac arrest and 5 mmHg 8 min after death; use of norepinephrine at the time of death was associated with higher Pmsf [24]. Pmsf can increase from 16 to 18 mmHg during infusion of vasoactive drugs [25]. Systemic venous stasis is the main clinical manifestation of constrictive pericarditis and is caused by right heart insu ciency [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported that Pmsf was 12 mmHg 1 minute after cardiac arrest and 5 mmHg 8 min after death; use of norepinephrine at the time of death was associated with higher Pmsf [24]. Pmsf can increase from 16 to 18 mmHg during infusion of vasoactive drugs [25]. Systemic venous stasis is the main clinical manifestation of constrictive pericarditis and is caused by right heart insu ciency [34].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in Pmsf re ect changes in circulating blood volume and indicate changes in volume status [12,15,16,21,22]. Pmsf varies according to clinical condition, volume status, and vasodilatory tone [23] and increases after uid infusion and vasopressor administration [24,25]. In patients receiving positive pressure ventilation, elevated RAP causes an increase in Pmsf to maintain an adequate venous return pressure gradient [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Preserved right ventricular function ensures that right atrial pressure is lower than Pmsa, thus providing driving pressure for venous return which is equal to cardiac output [ 18 ]. These physiological concepts of Pmsa and venous return were recently further clinically validated [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…We fully agree with this statement and further add that the data are complicated by variable disease stages and severity, different methodologies and high variability of volume status and/or catecholamine therapy. To illustrate the complexity of these mechanisms, a recent meta-analysis calculated the MSFP analogue of 28 studies and found that it increased in response to vasopressor infusion but with variable effects on central venous pressure and the pump efficiency of the heart leading to heterogenous changes in cardiac output 5 . Hyperdynamic states, the extent of capillary leakage, the vasoplegia, a reduced plasma volume as well as cardiac dysfunction are highly variable factors influencing the MCFP.…”
mentioning
confidence: 99%